Impact of COVID-19 on chronic disease management - Sama, Srikar; Gajjala, Alekhya (International Journal of Research in Medical Sciences, 2021)
Routine care for chronic disease is an ongoing major challenge. We aimed to evaluate the impact of COVID-19 on routine care for chronic diseases. A deeper understanding helps to increase the health system’s resilience and adequately prepare for the next waves of the pandemic. Diabetes, heart failure, chronic kidney disease, and hypertension were the most impacted conditions due to the reduction in access to care. It is important routine care continues in spite of the pandemic, to avoid a rise in non-COVID-19-related morbidity and mortality. This is a review article discussing the potential impact of COVID-19 on chronic disease management.